2009
DOI: 10.1111/j.1467-9906.2009.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity in Spillover Effects of Assisted and Unassisted Rental Housing

Abstract: Three new contributions are added to the literature on subsidized rental housing impacts on nearby property values: (1) a primary focus on the spatial heterogeneity of these effects that warrants caution regarding citywide results, (2) an analysis by zoning area, and (3) a comparison of impacts with unsubsidized apartments. An adjusted-interrupted time-series (difference-indifference) model is estimated with a comprehensive data set for Seattle, Washington (1987-1997. Contrary to not in my backyard (NIMBY) exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 42 publications
(64 reference statements)
2
43
0
1
Order By: Relevance
“…1 However, the findings in previous studies examining whether subsidized housing has negative impacts on nearby property values have been inconsistent. Some researchers who found negative impacts of subsidized housing point to the influx of "undesirables" as the cause of neighborhood decline (Cummings & Landis, 1993;Lee et al, 1999), while others suggested that subsidized housing developments lead to neighborhood revitalization by eliminating disamenities in neighborhoods (Baum-Snow & Marion, 2009; Koschinsky, 2009;Schwartz et al, 2006). However, support for public housing developments eroded in the 1980s (Eriksen & Rosenthal, 2010).…”
Section: Lihtc Subsidized Housing Developments In the Usmentioning
confidence: 94%
See 2 more Smart Citations
“…1 However, the findings in previous studies examining whether subsidized housing has negative impacts on nearby property values have been inconsistent. Some researchers who found negative impacts of subsidized housing point to the influx of "undesirables" as the cause of neighborhood decline (Cummings & Landis, 1993;Lee et al, 1999), while others suggested that subsidized housing developments lead to neighborhood revitalization by eliminating disamenities in neighborhoods (Baum-Snow & Marion, 2009; Koschinsky, 2009;Schwartz et al, 2006). However, support for public housing developments eroded in the 1980s (Eriksen & Rosenthal, 2010).…”
Section: Lihtc Subsidized Housing Developments In the Usmentioning
confidence: 94%
“…The underlying concept of the AITSeDID model is comparing the levels and trends of crime rates in neighborhoods with a LIHTC site before and after it was developed with those in other neighborhoods across the city where a LIHTC site was not developed (Galster et al, 2002;Koschinsky, 2009;Santiago et al, 2003;Woo et al, 2015). Thus, the model clarifies the causal direction of impacts of LIHTC developments by projecting the pre-development level and trend of crime rates in the neighborhood into the post-development period, while accounting for changes in city-wide crime trends .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previous studies have argued, the impacts of affordable housing projects can differ significantly in different neighborhood contexts (Freeman & Botein, 2002;Koschinsky, 2009). It is thus important to know where the LIHTC projects have been built in Santa Clara County.…”
Section: Where Have the Lihtc Projects Been Built?mentioning
confidence: 99%
“…Clearly, one could argue that there might be some selection bias in conducting the study in Santa Clara County, given the tight market environment within which the LIHTC projects have been built. For example, several existing studies have argued that affordable housing developments may be less likely to have negative impacts in tight housing markets than in declining markets (Koschinsky, 2009; Schwartz et al, 2006; Briggs et al, 1999). While this might be the case, it is also important to note that as a suburban metropolis, Santa Clara County, including its core city of San Jose, has a landscape that is largely dominated by low‐density developments.…”
mentioning
confidence: 99%